El acto notarial de permiso de salida del país y el rol del notario en la migración de los niños menores de edad - Rodríguez Revelo, Natalia Lissette (2026)
The authorization to leave the country granted before a notary public plays a decisive role in safeguarding the welfare of minors in the face of their increasing irregular migration; hence, it is relevant to know the role, functions, powers and limitations that the notary has in the practice of such a request. To this end, the objective was to study the principles of legal certainty, due diligence, interpretation, and the principle of rogation, in order to establish the cases in which the notary could refuse to issue such permits. The research methodology used has a qualitative approach with explanatory scope that legally analyzes concepts related to the subject, the applicable regulations and the principles regarding the attribution of the notary to grant permits to leave the country, which provide a theoretical orientation of the research from the bibliographic, legal and doctrinal review, executing content analysis to study the information collected. Among the results, it is noted that the notary public fulfills a public function and is dedicated to develop his attributions fulfilling a preventive or precautionary function oriented to provide certainty in legal relations through a diligent notarial performance. Finally, the researcher’s conclusive reflections are presented, from which it is observed that the State through the notary must guarantee a legitimate exercise of the right to the best interest of the child when issuing the permission to leave the country, which in no case should be at odds with the prohibitions of the notary’s activity.